PARTISIPASI POLITIK MASYARAKAT DALAM PEMILIHAN KEPALA DAERAH (STUDI PARTISIPASI POLITIK MASYARAKAT DI KELURAHAN UJUNG KECAMATAN SEMAMPIR KOTA SURABAYA DALAM PILKADA JAWA TIMUR 2018) - Moch. Razy Fatahilah (Aplikasi Administrasi: Media Analisa Masalah Administrasi, 2019)
This study analyzes the community political participation in East Java regional election. It aims to understand the affecting factors on the community political participation in Surabaya. The theory uses political participation. There are five indicators that influence political participation, such as social and economic status, parents’ affiliation, experience to organize, political awareness and confidence in the government. The research method is a qualitative descriptive method. data collection techniques are obtained through interview and documentation. The results indicate that the factors have greater influence on participation in social status and economics, and parents’ affiliation. Thus, it needs an urban village general election commission or educate for the residents who live in the urban village. Furthermore, the community work and the role of family in understanding the knowledge of politics have less supportive affiliation.